Strategic Planning Through Sport Events Leveraging Essentially - Zemikael Getu; Amelia Amelia (Journal Research of Social Science, Economics, and Management, 2023)
Events tourism is recognized as a significant and essential part of economic development strategies in developing countries as this industry affects the economy and the development of tourist destinations. Globally, many destinations are exploiting sport events as a strategic tool for energizing and themselves. In recent years, it has been widely accepted by tourism destination managers that sport events tourism make huge contributions to the tourism industry and the economy through foreign capital inflows. Various studies demonstrate that there is growing interest or even hunger to host sport events tourism as promoting development is evident in both developing and developed countries. Events tourism has demonstrated a significant growth over the years in both developing and developed countries. Nowadays, events are utilized as catalysts to develop and market host destinations. Therefore, the image of the host destination can improve and this can potentially lead to an influx of tourists to the host destination. Sporting events benefit destinations in various ways such as the infrastructural developments, foreign investment and foreign exchange, which leads to entrepreneurial opportunities.